IMPLEMENTASI NILAI-NILAI KEARIFAN LOKAL DALAM MENGEMBANGKAN KETERAMPILAN KEWARGANEGARAAN (Studi Deskriptif Analitik Pada Masyarakat Talang Mamak Kec. Rakit Kulim, Kab. Indragiri Hulu Provinsi Riau) - Ade, Verawati; Affandi, Idrus (Universitas Pendidikan Indonesia, 2016)
This research is motivated impact of globalization so that the degradation of culture and local wisdom, lack of awareness in the preservation of the culture and values of local wisdom study aims to describe the cultural part of civic skills, behaviors that reflect civic skills, citizenship skills development, constraints and efforts in conservation. So it needs to assess the values of local wisdom as civic skills in Talang Mamak tribe culture. A qualitative approach with descriptive analytic method. The findings of this study were 1) Talang Mamak tribe has a culture of mutual trust are values, attitudes ability to work together, trust, responsibility, solidarity, consensus, unity, and mutual cooperation. 2) Talang Mamak have local knowledge as a guide to behaving that reflects the behavior of citizenship skills are value patriotism, the value of equality, caring, responsibility, independence and the value of educational value. 3) the development of citizenship skills is done by carrying out traditional ceremonies, instilling the values of culture and local wisdom, and follow the cultural events organized by the government and society. 4) constraints contained in the preservation of culture and values of local wisdom that economic factors, educational factors, factors of confidence, and transportation factors.Keywords: cultural Talang Mamak Ethnicity, local wisdom, civic skills.